Anxiety, depression and coping of children with chronic kidney disease and their caregivers during the COVID-19 pandemic - YILDIZ, NURDAN; ÇİÇEK DENİZ, NESLİHAN; DEMİRCİ BODUR, ECE; ALPAY, HARİKA (My University, 2021)
Introduction: In this study, we aimed to evaluate our patients with chronic kidney disease(CKD) or kidney transplant recipients(KTx) and their parent’s/caregiver’s anxiety and depression levels and abilities of coping with difficulties during the COVID-19 pandemic. Material and methods: This cross-sectional study was conducted on 80 children with predialysis CKD, children on dialysis and KTx, 30 healthy children between 7-18 years of age and their care providers. Children were surveyed by the Strengths and Difficulties Questionnaire(SOQ-T), Screen for Child Anxiety Related Disorders(SCARED), childhood depression inventory and parents or caregivers by Coping Attitudes Assessment Scale(COPE), Beck Depression Inventory and Beck Anxiety Inventory.All questionnaires were done face-to-face or by phone and scored in accordance with the scales. Results: Signs of anxiety (SCARED scores) was present in 26(32.5%) patients and 4(13.3%) controls, and significantly higher in children with CKD and KTx recipients (p=0.03). Sixty-nine children and all controls have a depression scale of >19 and control group showed significantly higher depression scores than the patients (mean±SD,51.6±2.8 vs. 47.5±11.1; respectively, p=0.009). Thirteen (16.3%) patient and 2(6.7%) controls have high SDQDysregulation Profile(SDQ-DP) scores. SDQ-DP scores of the patients were significantly higher than the controls (9.6±5.3 vs. 7.2 ±5.8, respectively; p=0.000). There was no significant difference of mothers in coping with difficulties, anxiety and depression scores between the groups(p>0.05). Higher degree of anxiety of the patients was significantly associated with higher anxiety and depression symptoms of the mothers in the patients group (r=0.5, p=0.000 and r=0.435,p=0.001;respectively ),whereas there was no relationship between the SDQ-DP of the patients and Beck anxiety and depression scores of the mothers Conclusions: The COVID-19 outbreak causes increased anxiety in children with CKD and KTx and increased depression in healthy children. We may speculate that higher depression scores in healthy children may be due to sudden lifestyle restrictions during the pandemic compared to CKD patients who already have certain restrictions. The association of the increased anxiety of the patients with the depression and anxiety of the mothers has shown the necessity of more attention from mental health practitioners. Identifying affected children as early as possible and providing professional psychological and behavioral interventions will ensure a better mental health for children with chronic kidney diseases and their caregivers during the pandemic.